Spotlight on TAP and its vital role in antigen presentation and cross-presentation. (February 2022) - Mantel, Ian; Sadiq, Barzan A.; Blander, J. Magarian
Abstract: In the late 1980s and early 1990s, the hunt for a transporter molecule ostensibly responsible for the translocation of peptides across the endoplasmic reticulum (ER) membrane yielded the successful discovery of transporter associated with antigen processing (TAP) protein. TAP is a heterodimer complex comprised of TAP1 and TAP2, which utilizes ATP to transport cytosolic peptides into the ER across its membrane. In the ER, together with other components it forms the peptide loading complex (PLC), which directs loading of high affinity peptides onto nascent major histocompatibility complex class I (MHC-I) molecules that are then transported to the cell surface for presentation to CD8 + T cells. TAP also plays a crucial role in transporting peptides into phagosomes and endosomes during cross-presentation in dendritic cells (DCs). Because of the critical role that TAP plays in both classical MHC-I presentation and cross-presentation, its expression and function are often compromised by numerous types of cancers and viruses to evade recognition by cytotoxic CD8 T cells. Here we review the discovery and function of TAP with a major focus on its role in cross-presentation in DCs. We discuss a recently described emergency route of noncanonical cross-presentation that is mobilized in DCs upon TAP blockade to restore CD8 T cell cross-priming. We also discuss the various strategies employed by cancer cells and viruses to target TAP expression or function to evade immunosurveillance - along with some strategies by which the repertoire of peptides presented by cells which downregulate TAP can be targeted as a therapeutic strategy to mobilize a TAP-independent CD8 T cell response. Lastly, we discuss TAP polymorphisms and the role of TAP in inherited disorders.